2016
DOI: 10.1038/srep24039
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Deletion of Fgfr3 in Chondrocytes leads to Osteoarthritis-like Defects in Temporomandibular Joint of Adult Mice

Abstract: Osteoarthritis (OA) in the temporomandibular joint (TMJ) is a common degenerative disease in adult, which is characterized by progressive destruction of the articular cartilage. To investigate the role of FGFR3 in the homeostasis of TMJ cartilage during adult stage, we generated Fgfr3f/f; Col2a1-CreERT2 (Fgfr3 cKO) mice, in which Fgfr3 was deleted in chondrocytes at 2 months of age. OA-like defects were observed in Fgfr3 cKO TMJ cartilage. Immunohistochemical staining and quantitative real-time PCR analyses re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 59 publications
(81 reference statements)
3
36
0
1
Order By: Relevance
“…FGFR3, a receptor tyrosine kinase of FGF (FGF2 and FGF18) signaling, is expressed in the proliferating zone of the growth plate and acts to inhibit both chondrocyte proliferation and the initiation of chondrocyte hypertrophy through STAT1 and MAPK signaling 21 FGFR3 is also expressed in resting articular chondrocytes, but is downregulated during OA 33 . It has been recently shown that deletion of FGFR3 in chondrocytes leads to OA-like defects in the temporomandibular and knee joints in adult mice 34,35 , and FGFR3 activation attenuated cartilage degeneration induced by DMM surgery and age 36 . We found that mTORC1 activation reduced, while rapamycin increased FGFR3 expression both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…FGFR3, a receptor tyrosine kinase of FGF (FGF2 and FGF18) signaling, is expressed in the proliferating zone of the growth plate and acts to inhibit both chondrocyte proliferation and the initiation of chondrocyte hypertrophy through STAT1 and MAPK signaling 21 FGFR3 is also expressed in resting articular chondrocytes, but is downregulated during OA 33 . It has been recently shown that deletion of FGFR3 in chondrocytes leads to OA-like defects in the temporomandibular and knee joints in adult mice 34,35 , and FGFR3 activation attenuated cartilage degeneration induced by DMM surgery and age 36 . We found that mTORC1 activation reduced, while rapamycin increased FGFR3 expression both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…For histomorphometric analysis, the Safranin O-positive cartilage area and thickness were quantified by Image-Pro Plus 6.0 (Media Cybernetics, Bethesda, MD, USA). The Safranin O/Fast Green stained sections were used to examine the OA scoring using a modified Mankin's Score (mRS) system [20].…”
Section: Tunel and Safranin O-fast Green Stainingmentioning
confidence: 99%
“…Although numerous studies indicated the significant benefits of this mouse model, there is, to the best of our knowledge, no study investigating the biological processes of RA in the TMJ of the K/BxN mouse model. Compared to other joints in the body, the TMJ is so far unique, as it is exposed only to limited load‐bearing forces and it has different morphological, functional, biomechanical and biological features, especially because it contains fibrocartilage, primarily consisting of type I collagen, while the other joints mainly consist of hyaline cartilage, which is entirely based upon type II collagen …”
Section: Introductionmentioning
confidence: 99%